Functional Validation of CLDN Variants Identified in a Neural Tube Defect Cohort Demonstrates Their Contribution to Neural Tube Defects - Baumholtz, Amanda I.; De Marco, Patrizia; Capra, Valeria; Ryan, Aimee K. (Frontiers in Neuroscience, 2020)
Neural tube defects (NTDs) are severe malformations of the central nervous system that affect 1-2 individuals per 2000 births. Their etiology is complex and involves both genetic and environmental factors. Our recent discovery that simultaneous removal of Cldn3, -4 and -8 from tight junctions results in cranial and spinal NTDs in both chick and mouse embryos suggests that claudins play a conserved role in neural tube closure in vertebrates. To determine if claudins were associated with NTDs in humans, we used a Fluidigm next generation sequencing approach to identify genetic variants in CLDN loci in 152 patients with spinal NTDs. We identified eleven rare and four novel missense mutations in ten CLDN genes. In vivo validation of variant pathogenicity using a chick embryo model system revealed that overexpression of four variants caused a significant increase in NTDs: CLDN3 A128T, CLDN8 P216L, CLDN19 I22T and E209G. Our data implicate rare missense variants in CLDN genes as risk factors for spinal NTDs and identify a new family of proteins involved in the pathogenesis of these malformations.